Electrocardiogram in arrhytmogenic cardiomyopathy. (26th April 2023) - Calò, Leonardo; Oliviero, Giada; Crescenzi, Cinzia; Romeo, Fabiana; Martino, Annamaria; Bressi, Edoardo; Stefanini, Matteo; Silvetti, Elisa; Danza, Ludovica; Rebecchi, Marco; Canestrelli, Stefano; Fedele, Elisa; et al.
Abstract: Criteria for diagnosis of arrhythmogenic cardiomyopathy (ACM) were first proposed in 1994 and subsequently revised in 2010 and in 2020 by an international task force. According to the last consensus of 2020, ACM is defined as a heart muscle disease affecting right ventricle, left ventricle or both, whose principal pathologic feature is fibrofatty myocardial replacement that impairs systolic ventricular function and predisposes to lethal ventricular arrhythmias. ECG findings not only could help to early recognize affected patients but also could identify the ones with maximum risk of ventricular arrhythmias and sudden cardiac death.